2018
DOI: 10.1186/s13567-018-0615-x
|View full text |Cite
|
Sign up to set email alerts
|

First demonstration of the circulation of a pneumovirus in French pigs by detection of anti-swine orthopneumovirus nucleoprotein antibodies

Abstract: The presence of pneumoviruses in pigs is poorly documented. In this study, we used the published sequence of the nucleoprotein (N) of the recently identified Swine Orthopneumovirus (SOV) to express and purify SOV N as a recombinant protein in Escherichia coli. This protein was purified as nanorings and used to set up an enzyme-linked immunosorbent assay, which was used to analyse the presence of anti-pneumovirus N antibodies in swine sera. Sera collected from different pig farms in the West of France and from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Although SOV infections have been reported in the USA, Spain, and France [2,4,13], only one complete genome sequence has been reported from the USA in 2016 [2]. Therefore, viral gene sequencing was carried out to further characterize the Korean SOVs.…”
Section: Resultsmentioning
confidence: 99%
“…Although SOV infections have been reported in the USA, Spain, and France [2,4,13], only one complete genome sequence has been reported from the USA in 2016 [2]. Therefore, viral gene sequencing was carried out to further characterize the Korean SOVs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the discovery of SOV in the USA suggests that yet unknown pneumoviruses could be responsible for respiratory diseases in other animal species. A recent study suggested a high prevalence of this virus in France [30]. However, further studies are required to determine whether this virus is pathogenic for pigs.…”
Section: Impact Of Infections By Pneumoviridaementioning
confidence: 99%
“…Among them, it is worth mentioning Influenza B (IBV) and D (IDV) ( 20 23 ), swine orthopneumovirus (SOV) ( 24 ), porcine parainfluenza 1 virus (PPIV1, also designated as porcine respirovirus ) ( 25 27 ), and porcine circovirus 3 (PCV3) ( 28 ). The knowledge on the epidemiology of these viruses, their interactions and participation in respiratory disease is limited, with only a few reports available ( 29 33 ). The role of other recently discovered agents, such as PCV4 ( 34 ) is not known yet ( 35 ).…”
Section: Introductionmentioning
confidence: 99%